Cell biology and histology in medicine: perception on education and student performance - Ana Laura Sandoval Mantovani; Alba Regina De Abreu Lima; Sérgio Luís Aparecido Brienze; Emerson Roberto dos Santos; Patrícia da Silva Fucuta; Júlio César André (Escola Bahiana de Medicina e Saúde Pública, 2019)
The subjects areas of Cellular Biology and Histology, which underpin the microscopic field of Morphology and are included in the first years of the curriculum in a Medical course, are the pillars of medical education  and for the clinical reasoning of future professionals. This study aimed to trace a teaching profile of Cellular Biology and Histology in the Medical courses which had participants in the selection process to fill vacancies by transfer, for the undergraduate course in the Medical School of São José do Rio Preto (FAMERP)  in 2017. This was a quantitative and qualitative cross-sectional study and 132 academics participated. The results showed that, in most Higher Education Institutions, these disciplines are taught theoretically and practically. In the comparison between the theoretical performance of the students of traditional and active teaching-learning methodology, a higher number of hits in Histology and a better final grade were observed in the traditional. The deficiency pointed out by the students was a lack of laboratory sessions with viewing histological glass slides with light microscopes. Also, the aspect of teachers' pedagogical practice and dynamic classes was shown to be fundamental to the students' interest, as well as to better satisfaction's index in learning these areas. Furthermore, integrating these disciplines with the clinical practice of Medicine has proved to be relevant for academics, who feel more instigated to knowledge. In the present study, it was detected a better use in relation to the Histology by the students of the courses of traditional methodology, compared to those of active methodology and in this way the analysis done can to collaborate for the enrichment and reaffirmation of the fruits of the comparison of teaching-learning methodologies.